Russia's debt crisis and the unofficial economy - Mechthild Schrooten; Lusine Lusinyan; Ralph P. Heinrich; Claudia M. Buch (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Russia's foreign debt problems worsened substantially after the financial crisis of 1998. The paper focuses on the key role of the government in servicing foreign debt and promoting institution building by showing how foreign debt influences the choice between official and unofficial taxation. The enterprise sector is assumed to reallocate its resources between domestic investment and capital flight. It is discussed under which conditions debt rescheduling may create incentives for the government to promote institution building. The results of this paper shed light on the conditions under which the recent agreement with the London Club to write off substantial amounts of former Soviet debt can be successful.
Keywords: H63; F34; 330; Foreign debt; debt restructuring; Russian Federation; Auslandsverschuldung; Auslandsschuldendienst; Steuerpolitik; Schattenwirtschaft; Unternehmensbesteuerung; Kapitalflucht; Umschuldung; Theorie; Russland